THE INFLUENCE OF INCOME ADEQUACY, WORK-LIFE BALANCE, PERCEIVED ORGANIZATIONAL SUPPORT, AND PSYCHOLOGICAL WELL-BEING ON THE PERFORMANCE OF MADRASAH IBTIDAIYAH TEACHERS IN JEPARA REGENCY - Muhammad Khoirul Anam; Sisno Riyoko; Ali Ali (JURNAL ILMIAH EDUNOMIKA, 2026)
Human resource management emphasizes the importance of employees’ psychological conditions and organizational support in improving individual performance. In the workplace, employee performance is influenced not only by financial factors but also by work-life balance, perceived organizational support, and psychological well-being. Teachers, as human resources within educational organizations, are expected to maintain high levels of performance while managing work demands and personal responsibilities. Therefore, understanding the factors that influence teachers’ psychological well-being and performance is essential from a human resource management perspective. This study aims to examine the effects of income adequacy, work-life balance, and perceived organizational support on psychological well-being and teacher performance among Madrasah Ibtidaiyah teachers in Jepara Regency. The sampling technique employed was purposive sampling based on predetermined criteria: (1) active teachers at Madrasah Ibtidaiyah in Jepara Regency; (2) having at least one year of teaching experience; and (3) willingness to participate by completing the questionnaire. A total of 184 respondents were selected from a population of 340 teachers. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS version 3.29. The findings reveal that income adequacy has no significant effect on either psychological well-being or teacher performance. In contrast, work-life balance and perceived organizational support have positive and significant effects on both psychological well-being and teacher performance. Furthermore, psychological well-being has a positive and significant effect on teacher performance. These findings suggest that, from a human resource management perspective, organizational support and employees’ ability to maintain work-life balance are more influential in enhancing psychological well-being and performance than income adequacy alone. The study highlights the importance of organizational policies that foster supportive work environments and employee well-being to achieve sustainable performance.   Keywords: Income Adequacy, Work-Life Balance, Perceived Organizational Support, Psychological Well-Being, Teacher Performance